HUBUNGAN SOSIODEMOGRAFI DAN LINGKUNGAN FISIK DENGAN KEJADIAN DEMAM BERDARAH DEGUE (DBD) PADA MASYARAKAT PESISIR PANTAI KOTA TARAKAN (Studi Kasus Pada Daerah Buffer Kantor Kesehatan Pelabuhan Kelas II Tarakan) The Correlation of Sociodemographic and Ph - Wahyu Handoyo; Retno Hestinigsih; Martini Martini (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Dengue Hemorrhagic Fever (DHF) is a disease that is a health problem in Indonesia. Tarakan city within the last 4 years is constantly increasing number of dengue cases, as many as 409 cases with IR 194.3% per 100,000 population. While the Case Fatality Rate (CFR = 0.73%) greater than the national indicator (0.1%). The purpose of this study was to determine the relationship of sociodemographic, physical environment and karatristik individuals with incidence of dengue in the coastal communities buffer area port health office class II of Tarakan. This type of research is analytic observational study with survey and interview. The design of the study using cross-sectional. Population is head of the family or a housewife with a sample of 138 respondents. Sampling using random sample. Data were analyzed by Chi-square test (X2) with a significance level of 95% and the value of α = 0.05. The results showed that out of town / mobility obtained pOR = 17.051 residents out of the city means 17 are more at risk of dengue fever than those who do not get out of town. The existence of larvae obtained pOR = 7.604 means that the house contained 7.6 larvae are particularly susceptible to dengue than homes that are not contained larvae. Incidence of dengue was no correlation with the level of education, sex, age, residential density, Characteristics of the home, where the lid containers, knowledge, attitudes and practices (p> 0.05). Eradication of Mosquito Breeding (PSN) needs to be done, fostering cadres, and Community Empowerment.